Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00431-010-1282-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical incidents in paediatric critical care: who is at risk?

Abstract: We evaluated the characteristics of children for whom critical incidents (CIs) were reported by performing prospective collection of patient data and retrospective review of reported CIs in a multidisciplinary neonatal-paediatric intensive care unit of a tertiary care university children's hospital. A period of 1 year was analysed (January to December 2007; 1,251 admissions). CIs comprised adverse events (actual patient injury), as well as near-misses. The report form of critical incidents was web-based and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Younger patients and patients with prolonged ventilator dependence were at higher risks of SEAEs. This finding is in accordance with the literature evaluating safety incidents in the PICU (21,22). Previous studies have established harm rates of 0.37 (9) and 0.40 (7) per admission using trigger lists to identify the most common causes of harm in pediatric inpatient environments.…”
Section: Discussionsupporting
confidence: 90%
“…Younger patients and patients with prolonged ventilator dependence were at higher risks of SEAEs. This finding is in accordance with the literature evaluating safety incidents in the PICU (21,22). Previous studies have established harm rates of 0.37 (9) and 0.40 (7) per admission using trigger lists to identify the most common causes of harm in pediatric inpatient environments.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, minor errors were the most common, followed by moderate and severe errors. This agrees with a study that reported 61% minor errors, 26% moderate errors and 13% major errors (11). However, our results disagree with another study that reported 30% major errors (death or need for ICUspecific intervention), 25% moderate errors (requiring routine therapy available outside the ICU) and 45% minor errors (no intervention required) (27).…”
Section: Discussionsupporting
confidence: 70%
“…The incidence of AEs in the PICU population depends on the method used to detect AEs [1, 17, 19, 22, 28, 31, 33, 36]. Studies using a trigger tool method show that 59–76% of all PICU patients encounter at least one AE during their stay [1, 17, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Although one could speculate that AE incidence is higher in the more complex and sicker patients needing extensive support (high-risk patients), AEs also occur in the less severely ill PICU patients [1, 17, 22]. To our knowledge, no studies have focused on the occurrence of AEs in low-risk PICU patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation